Iron Deficiency Anemia and Neurologic Deficits - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
A 14 year old black female adolescent with focal neurological abnormalities complicating severe iron deficiency anemia is reported from Duke University Medical Center, Durham, North Carolina.